Analyzing the Responsiveness of Non-Bank Financial Institutions in Digital Marketing: A Case Study of BMT in West Nusa Tenggara - Riduan Mas’ud; Muhammad Azizurrohman (International Business and Accounting Research Journal, 2022)
Banks and non-bank financial institutions must adapt to the rapid advancement of technology. This is owing to shifts in people's consumption behaviors around the world, who formerly used traditional methods and are now transitioning to digital ones. The development of numerous forms of financial services that make it easier for customers to transact is aided by technological sophistication. Baitul Maal Wat Tamwil (BMT) is a non-bank financial institution that serves the lower middle class with financial services. As a result, it is critical to take several strategic initiatives to expand the organization's position in community assistance. This research intends to propose an alternate strategy for BMTs in expanding their institutions in the contemporary digital era, particularly in West Nusa Tenggara. The authors used a snowball sampling methodology to collect data using a descriptive qualitative method and a literature review. BMT must take various steps, according to this study, including website marketing, search engine marketing, social media marketing, online advertising, email marketing, and video marketing. However, in West Nusa Tenggara, BMT has not taken a step forward in digital marketing. Only a few organizations have begun to see the value of digital marketing.